Gaining Ghost Town of Tourism Economics Northern Cyprus Varosha City - Sülün Evinç Torlak (European Scientific Journal, ESJ, 2016)
Ghost towns were abandoned places for same reasons such as disasters, economic collapse, disease, war. North Cyprus City’s Varosha is a ghost town. The city was received during the Turkey's Peace Operation. It has been closed until that time - 1974. It is under the control of UN and takes place in the Green Line buffer zone. The research is based on the site work. The data obtained from the local authority and information collected by interviews with local people. To be entered in the City with special permission and observation could be made in Varosha. Before 1974 Varosha is one of the most lively tourist center of the world. 200 billion euros investment needs for Its reconstruction. After reconstruction business volume of the region will be exploded. Without wasting more time, the City should be given to the tourism economy. However, the risk of deterioration of existing tissue will raise after opening of Varosha. The city has been witness to the period of the humanity history. There is no other city in the world having this property. Projects related to the City must be produce without losing its texture.Aimed of the study is that without lossing its features, put forward proposals for opening to tourism of the City. In this study recommendation for the City’s protection were developed. Based on the successful example of revived ghost town, a museum city proposal improved for Varosha.